2002
DOI: 10.1093/jac/dkf074
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of three new triazoles and one echinocandin against Candida bloodstream isolates from cancer patients

Abstract: The in vitro activities of voriconazole, posaconazole, ravuconazole and micafungin were compared with those of fluconazole, itraconazole, ketoconazole, flucytosine and amphotericin B against 164 candidaemia isolates recovered from cancer patients in two Canadian centres. The MIC(50) results for ravuconazole, voriconazole, posaconazole and micafungin were 0.01, 0.03, 0.12 and 0.25 mg/L, respectively. The new antifungal agents showed substantial activity against isolates demonstrating in vitro resistance to fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 10 publications
9
30
0
Order By: Relevance
“…This complies with a previous report, where C. albicans constituted 56.3% of patients receiving radiotherapy for head and neck neoplasms, while each of C. glabrata and C. tropicalis was present in 12.5% of the total patients (Tudela et al, 2002). Furthermore, most of the OPC samples from cancer patients in different regions were also identified as C. albicans with a range of 33 to 76% of the total isolates (Laverdiere et al, 2002;AlAbeid et al, 2004;Belazi et al, 2004). This study also showed higher prevalence of C. albicans in both solid and haematological cancer types, followed by C. krusei, then C. glabrata and finally, C. tropicalis in solid cancer types.…”
Section: Discussionsupporting
confidence: 91%
“…This complies with a previous report, where C. albicans constituted 56.3% of patients receiving radiotherapy for head and neck neoplasms, while each of C. glabrata and C. tropicalis was present in 12.5% of the total patients (Tudela et al, 2002). Furthermore, most of the OPC samples from cancer patients in different regions were also identified as C. albicans with a range of 33 to 76% of the total isolates (Laverdiere et al, 2002;AlAbeid et al, 2004;Belazi et al, 2004). This study also showed higher prevalence of C. albicans in both solid and haematological cancer types, followed by C. krusei, then C. glabrata and finally, C. tropicalis in solid cancer types.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in keeping with published work on yeasts from a range of other patient groups and body sites (Cuenca-Estrella et al, 1999;Pelletier et al, 2002;Laverdiere et al, 2002). Of particular relevance is the voriconazole susceptibility of the isolates that were resistant to fluconazole and itraconazole.…”
Section: Antifungals In Oral Fungal Infectionssupporting
confidence: 86%
“…Of particular relevance is the voriconazole susceptibility of the isolates that were resistant to fluconazole and itraconazole. Many of these strains displayed low MICs to voriconazole, confirming reports by others that this agent is of value in treating some infections involving fluconazoleresistant Candida species (Pelletier et al, 2002;Laverdiere et al, 2002). However, the MICs of voriconazole for flucona- zole-resistant isolates were higher than those for fluconazolesusceptible isolates, as reported by others (Cuenca-Estrella et al, 1999).…”
Section: Antifungals In Oral Fungal Infectionssupporting
confidence: 82%
“…32 Micafungin shows potent fungicidal activity against clinically isolated yeast species of Candida, including C. albicans, C. dubliniensis, C. tropicalis, C. glabrata and C. krusei, and against C. parapsilosis, C. lusitaniae and C. guilliermondii with slightly higher MIC 90 values. [33][34][35] No cross-resistance to fluconazole-resistant clinical isolates of Candida has been observed. 36 Characteristically, micafungin has potent in vitro inhibitory activity against Aspergillus species at lower concentrations than amphotericin B and itraconazole, but micafungin was not fungicidal against Aspergillus spp.…”
Section: Pre-clinical Study Of Fk463mentioning
confidence: 99%